Constitutions - Bryce, James Bryce, Viscount, 1838-1922. (New York : Oxford University Press, American Branch, 1905)
Six essays extracted from the author's "Studies in history and jurisprudence", published in 1901--Cf. pref. 1. Flexible and rigid constitutions -- 2. The action of centripetal and centrifugal forces on political constitutions -- 3. Primitive Iceland -- 4. The Constitution of the United States as seen in the past -- 5. Two South African constitutions -- 6. The constitution of the commonwealth of Australia. Mode of access: Internet.